Moving towards collaborative care in combating the burgeoning burden of tuberculosis and diabetes: key findings from a pharmaceutical care study / Shubashini Gnanasan ... [et al.] - Gnanasan, Shubashini; Muttalif, Abdul Razak; Mohd Ali, Salmiah; Kang, Nee Ting; Anderson, Claire (Faculty of Pharmacy, 2021)
Diabetes mellitus is one of the most common comorbidities in tuberculosis patients with prevalence as high as 15-30% in Malaysia. The convergence of these two diseases is linked to poorer tuberculosis treatment outcomes, increased chances of relapse and recurrence within two years, increased risk of multi drug resistant-tuberculosis, reactivation of latent tuberculosis infection and higher risk of death during tuberculosis treatment. It is imperative to have a collaborative effort from all stakeholders including pharmacists in order to establish a coordinated response to both diseases. This paper reports key findings of a mixed-method pharmaceutical care study that tackled many medication-related problems in patients with both tuberculosis and diabetes. Despite the need to address the barriers and challenges encountered during the provision of pharmaceutical care, pharmacists played an important role in promoting diabetes management in a tuberculosis clinic, and the integration of pharmacists within a multidisciplinary health care team was indeed feasible.